Identification of gene fusion events in Mycobacterium tuberculosis that encode chimeric proteins. Issue 2 (18th May 2020) - Gallant, James; Mouton, Jomien; Ummels, Roy; ten Hagen-Jongman, Corinne; Kriel, Nastassja; Pain, Arnab; Warren, Robin M; Bitter, Wilbert; Heunis, Tiaan; Sampson, Samantha L
Abstract: Mycobacterium tuberculosis is a facultative intracellular pathogen responsible for causing tuberculosis. The harsh environment in which M. tuberculosis survives requires this pathogen to continuously adapt in order to maintain an evolutionary advantage. However, the apparent absence of horizontal gene transfer in M. tuberculosis imposes restrictions in the ways by which evolution can occur. Large-scale changes in the genome can be introduced through genome reduction, recombination events and structural variation. Here, we identify a functional chimeric protein in the ppe38–71 locus, the absence of which is known to have an impact on protein secretion and virulence. To examine whether this approach was used more often by this pathogen, we further develop software that detects potential gene fusion events from multigene deletions using whole genome sequencing data. With this software we could identify a number of other putative gene fusion events within the genomes of M. tuberculosis isolates. We were able to demonstrate the expression of one of these gene fusions at the protein level using mass spectrometry. Therefore, gene fusions may provide an additional means of evolution for M. tuberculosis in its natural environment whereby novel chimeric proteins and functions can arise.